Configurational Entropy Relaxation of Silica Glass—Molecular Dynamics Simulations - Gedeon, Ondrej (Entropy (Basel), 2021)
Vitreous silica was modelled using molecular dynamics (MD). The glass structure was transferred into an undirected graph and decomposed into disjoint structural units that were ideally mixed to calculate the configurational entropy. The Debye relaxation model was suggested to simulate the evolution of entropy during the cooling of the system. It was found that the relaxation of the configurational entropy of MD corresponds to the effective cooling rate of 6.3 × 10(6) Ks(−1) and its extrapolation to 0.33 Ks(−1) mimics the glass transition with T(g); close to the experimental value. Debye relaxation correctly describes the observed MD evolution of configurational entropy and explains the existence of freezing-in temperature and the shape of the curve in the transition region.